2017
DOI: 10.1016/j.otsr.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The further exploration of hidden blood loss in posterior lumbar fusion surgery

Abstract: Our research is a case-control study and the level of proof is III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 11 publications
4
36
2
Order By: Relevance
“…It increased the visible blood loss (surgery bleeding plus drainage). [ 2 , 18 ] In our study, the intraoperative and postoperative visible blood loss were disregarded, thereby possible underestimating the amount of HBL.…”
Section: Discussionmentioning
confidence: 99%
“…It increased the visible blood loss (surgery bleeding plus drainage). [ 2 , 18 ] In our study, the intraoperative and postoperative visible blood loss were disregarded, thereby possible underestimating the amount of HBL.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 Additionally, these reviews have found antifibrinolytic use to significantly reduce postoperative blood loss, which is an often neglected contribution making up to 30% of total blood loss. 24 investigation was beyond the scope of the present study, one is able to extrapolate and assume that cost savings may increase as the invasiveness of the surgery increases (i.e., deformity and tumor cases). 1…”
Section: Evidence For the Use Of Txa In Spine Surgerymentioning
confidence: 99%
“…Sehat et al [2] proposed concept of HBL in 2000, which might be in association with negative postoperative outcomes [7,8]. According to published studies, the HBL in lumbar fusion surgery ranged from 227 to 600 ml, but most surgeons might ignore it [9][10][11]. A previous study showed that compared with open transforaminal lumbar interbody fusion (O-TLIF), HBL in patients undergoing MIS-TLIF was seriously underestimated, and accounted for a larger percentage of total blood loss (TBL) even though TBL after MIS-TLIF was much less [12].…”
Section: Introductionmentioning
confidence: 99%